Parenting: Family and Character manners of Children in Manleten Village Belu - Vanida Mundiarti; Yunita Seran; Sartika Kale (Early Childhood Education Development and Studies (ECEDS), 2022)
The family is the first learning environment for children, the family has a very important role in shaping the character of children's manners, related to this in this study was carried out in Manleten Village, Belu Regency, East Nusa Tenggara which aims to describe how the role of the family in shaping the character of children's manners. The research data is in the form of qualitatively descriptive data, research data was obtained through observations and interviews conducted for one month to sources who met the criteria as informants in the study, namely five fathers and five mothers, from children aged 5-6 years in Manleten Village. The validity of the research data through trianggulation of sources, namely by interviewing two teachers of the children. The results showed that in shaping the character of manners for children aged 5-6 years, families in Manleten Village have carried out their roles well, namely providing positive examples such as being friendly to guests, and speaking politely when speaking, accustoming children to say the words please, sorry, thank you, and greeting parents, the family creates a conducive atmosphere in the house by advising children and taking time for children. Broadly speaking, the role of the family in determining the character of children's manners in Manleten Village is divided into three main points, namely: 1) Character building through giving positive role models or role models; 2) Habituation; and 3) Creating a conducive atmosphere in the family.